Implementasi Demokrasi Ekonomi Sejak Diberlakukannya Undang-Undang Nomor 6 Tahun 2023 Penetapan Perppu Nomor 2 Tahun 2022 Tentang Cipta Kerja menjadi UU - Aini Shalihah; Lian Fawahan (Faculty of Law, Universitas Airlangga, 2023)
AbstractThis article aims to determine and analyze the legitimacy of actions the presence of Law Number 6 of 2023 concerning the Stipulation of Perppu Number 2 of 2022 concerning Job Creation cannot yet be said to be a solution to stabilize economic democracy in Indonesia. In terms of substance, the law contains several economic contents such as workers' wages and others. This is because there is still opposition from the public regarding this policy and the government, in the process of making the mechanism for this policy, is considered to have injured the Law on the Formation of Legislation, namely in terms of community participation. So then, the application or implementation of economic democracy in the field is still far from optimal. Because in this case the government often makes policies that do not involve public participation. So public participation in Law No. 6 of 2023 proves that economic democracy is currently still not resolved. Keywords: Democracy; Economy; Indonesia; Determination of Job Creation Perppu. AbstrakUndang-Undang Nomor 6 Tahun 2023 tentang Penetapan Perppu Nomor 2 Tahun 2022 tentang Cipta Kerja masih belum bisa dikatakan sebagai solusi untuk menstabilkan demokrasi ekonomi di Indonesia. UU tersebut dalam hal substansi mengandung beberapa muatanmuatan ekonomi seperti halnya upah pekerja maupun yang lain. Hal ini disebabkan karena masih ada pertentangan dari masyarakat terkait kebijakan ini serta pemerintah dalam proses mekanisme pembuatan dari kebijakan ini dianggap menciderai UU Pembentukan Peraturan Perundang-undangan yakni dalam hal partisipasi masyarakat. Sehingga kemudian, penerapan ataupun pelaksanaan demokrasi ekonomi di lapangan masih jauh dari kata maksimal. Dikarenakan dalam hal ini pemerintah sering membuat kebijakan yang belum melibatkan partisipasi publik. Jadi public participation dalam UU No.6 Tahun 2023 membuktikan bahwa demokrasi ekonomi saat ini masih belum teratasi. Kata Kunci: Demokrasi; Ekonomi; Indonesia; Penetapan Perppu Cipta Kerja.